The Education of the Eye History of the Royal Polytechnic Institution 1838-1881 - Weeden, Brenda (University of Westminster Press, 2008)
"The Royal Polytechnic Institution's story is the first episode in the long, diverse history of the University of Westminster. Drawing on an extensive range of primary and secondary sources this book explores the Institution's reputation for visual spectacle and the popularisation of science. It is lavishly illustrated with contemporary images. A print paperback can be purchased direct from the University of Westminster for £20 following this link: www.westminster.ac.uk/historybooks Staff, students and alumni can claim a 20% discount on this price."